2020
DOI: 10.1111/joor.13085
|View full text |Cite
|
Sign up to set email alerts
|

The role of progressive oral implant rehabilitation in mastication, cognition and oral health‐related quality of life outcomes—A pilot to define the protocol

Abstract: Background The implications of oral rehabilitation after tooth loss require further investigation. Objectives To conduct a pilot study to investigate: (a) changes in masticatory performance with progressive oral implant rehabilitation (POR); (b) association between POR and neurocognitive function using functional magnetic resonance imaging (fMRI); and (c) oral health‐related quality of life (OHQoL) outcomes. Methods Four completely edentulous patients (mean age: 73 ± 1.4 years) participated. Each received new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 123 publications
(360 reference statements)
0
23
0
1
Order By: Relevance
“…The current lack of knowledge in this cause-effect association likely derives from the fact that there is a paucity of well-conducted prospective clinical studies investigating the association between edentulism and cognition. In our assessment of the literature in this particular topic, we have been able to identify only one pilot study [41], and two protocols for clinical studies, one set in Sweden published in 2021 [42] and the other one, registered in 2016 and still ongoing, by our own group in Spain [43].…”
Section: Discussionmentioning
confidence: 99%
“…The current lack of knowledge in this cause-effect association likely derives from the fact that there is a paucity of well-conducted prospective clinical studies investigating the association between edentulism and cognition. In our assessment of the literature in this particular topic, we have been able to identify only one pilot study [41], and two protocols for clinical studies, one set in Sweden published in 2021 [42] and the other one, registered in 2016 and still ongoing, by our own group in Spain [43].…”
Section: Discussionmentioning
confidence: 99%
“…Confounding factors such as sarcopenia, adaptive capacities and adjustments of diet consistency due to loss of teeth can influence the secondary outcome parameters. However, a recent preliminary study with similar study objectives has with a smaller sample shown promising results [59]. Successive studies will be planned to consider all the major confounding factors reflecting on the results of the current study and perhaps follow the participants in the current study for a longer duration.…”
Section: Discussionmentioning
confidence: 98%
“…Many clinical studies have shown that chewing exercise can be considered as a preventive method for cognitive impairment (Ono et al, 2010;Tada and Miura, 2017;Chuhuaicura et al, 2019). Corresponding results appeared after the use of implants or dentures to repair the missing teeth, patients' cognitive level can be improved (Ki et al, 2019;Tan et al, 2020). Avivi-Arber et al (2015) have proved that the neural plasticity of the facial primary motor cortex (FACE-M1) and the adjacent primary somatosensory cortex (FACE-S1) of rats was enhanced after the implantation.…”
Section: Discussionmentioning
confidence: 99%